Comparative Effectiveness of Exercise Training for Patients With Chronic Thromboembolic Pulmonary Hypertension After Pulmonary Endarterectomy: A Systematic Review and Meta-Analysis - Zhao, Ya-Lin; Yuan, Ping; Zhao, Qin-Hua; Gong, Su-Gang; Zhang, Rui; He, Jing; Luo, Ci-Jun; Qiu, Hong-Ling; Liu, Jin-Ming; Wang, Lan; Jiang, Rong (Frontiers in Cardiovascular Medicine, 2021)
Background After undergoing pulmonary endarterectomy (PEA), patients with chronic thromboembolic pulmonary hypertension (CTEPH) still experience reduced exercise capacity. Exercise training is thought to improve exercise capacity and quality of life (QoL) in patients with PH, but data on the effects of exercise training in these patients are scarce. The aim of meta-analysis was to evaluate the effectiveness and safety of exercise training in CTEPH after PEA. Methods A search for relevant literature was conducted for the meta-analysis using the PubMed, EMBASE, and Cochrane Library databases, and literature published before December 2020 was included. The primary outcome was a change in six-minute walk distance (6MWD). We also assessed the effect of exercise on peak oxygen uptake (peak VO2) or peak VO2/kg, oxygen uptake anaerobic threshold, workload, oxygen pulse, haemodynamics, arterial blood gases, oxygen saturation, N-terminal pro-brain-type natriuretic peptide (NT-proBNP), QoL and pulmonary function tests. Results A total of 4 studies with 208 exercise-training participants were included. In the pooled analysis, exercise training after PEA was associated with a significant improvement in 6MWD [weighted mean difference (WMD): 57.58 m (95% CI: 45.73 to 69.40) and 51.00 m (95% CI: 42.36 to 64.40) at 3 or 12/15 weeks, both P < 0.001], peak VO2/kg and peak VO2 at 12/15 weeks [WMD: 3.19 ml/min/kg (95% CI: 0.77 to 5.61), P = 0.003; WMD: 316.06 ml/min (95% CI: 67.82 to 564.31), P = 0.008], right ventricular ejection fraction (RVEF) [WMD: 3.53% (95% CI: 6.31 to 11.94), P < 0.00001], NT-proBNP plasma levels (WMD: 601.92 ng/L, 95% CI: 276.52 to 927.31, P < 0.001) and QoL measured by the SF-36 questionnaire. Partial pressure of oxygen and pH improved progressively over 12 weeks of exercise training after PEA (WMD: 4 mmHg, 95% CI: 1.01 to 8.33, P = 0.01; WMD: 0.03, 95% CI: 0.02 to 0.04, P < 0.0001, respectively). Furthermore, exercise training was well tolerated with a low dropout rate, and no major adverse events were found to be related to exercise training. Conclusion Exercise training in CTEPH patients after PEA is associated with significant improvements in exercise capacity, RVEF, arterial blood gases, NT-proBNP and QoL.